PENGUKURAN KUANTITAS UAP MASUK REBUSAN SECARA TIDAK LANGSUNG MENGGUNAKAN GRAFIK ROTOTHERM - Heri Purwanto; Ika Ucha P.Rangkuti (Institut Teknologi Sawit Indonesia (ITSI), 2020)
Sterilization process is one of the keys to success in a Palm Oil Mill. In conventional palm oil mills that usehorizontal serilization, the fruit is heated in a closed vessel using pressurized steam at a pressure of 40 psiand a temperature of 140oC. The performance parameters that determine the success of the process inintermediate sterilization are pressure, temperature and time as well as steam requirements. This study aimsto determine the correlation between the area under sterilization graph represent the measurement of timeand pressure from every cycle of sterilization to oil losses in the condensate and empty bunch. The resultsshow that the higher the sterilization graph area which represents pressure and time, did not show significanttrend to the percentage of oil losses in the condensate and emptu bunch.